High DNA Uptake Capacity of International Clone II Acinetobacter baumannii Detected by a Novel Planktonic Natural Transformation Assay - Hu, Yuan; He, Lihua; Tao, Xiaoxia; Meng, Fanliang; Zhang, Jianzhong (Frontiers in Microbiology, 2019)
Acquisition of novel resistance genes is a key driver of multidrug resistance in the nosocomial pathogen Acinetobacter baumannii. To investigate the DNA uptake ability among clinical A. baumannii strains, a planktonic salt-free transformation assay was developed. A total of 142 clinical A. baumannii isolates with divergent genetic distance were selected, and 86 of them belong to international clonal lineage II (ICL2). Using this new transformation assay, 38% of the clinical A. baumannii isolates were natural competent. Among the multidrug-resistant (MDR) isolates, the transformable isolates all belonging to the ICLs, and showed significant higher transformation frequency compared with sensitive isolates. In addition, some of the ICL2 isolates triggered competence much earlier than the sensitive isolates with similar transformation frequencies. This may give them more opportunities to obtain successful transformation in their natural environment and provides an important clue to explain the severe drug resistance and clinical successfulness of ICL2.